2016
DOI: 10.1021/acs.cgd.5b01785
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Formation Mechanism of Textured MOF-5

Abstract: Textured and house-of-card structures develop on the surfaces of cubic MOF-5 crystals. The formation mechanism of these novel constructions are investigated based on characterisation of the intermediate specimens with different reaction time intervals using scanning and transmission electron microscopies. It is found that the growth of MOF-5 cubic crystals does not follow the classical route. MOF-5 nanocrystallites initially aggregate to form large polycrystalline cubes, followed by surface rearrangement of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 47 publications
4
32
0
Order By: Relevance
“…The XRD pattern of IRMOF‐1 is in good consistency to previous reports . Also sharpness and high intensity of the peaks indicate high crystallinity of the materials …”
Section: Resultssupporting
confidence: 89%
“…The XRD pattern of IRMOF‐1 is in good consistency to previous reports . Also sharpness and high intensity of the peaks indicate high crystallinity of the materials …”
Section: Resultssupporting
confidence: 89%
“…Greer et al . 62 concluded that the crystallisation proceeds via a reversed crystal growth route in which oriented aggregation of initially formed nanocrystallites is promoted by DBA also acting as surface ligand and spacer. In later stages, recrystallization occurs from the surface to the core.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, they underwent aggregation to form polycrystalline particles with a rhombohedral appearance (Figure 7d). Despite the short history of this reversed crystal growth route it has been used to explain the formation of many hollow and core-shell crystals in several inorganic systems including zeolites [48,74,75], perovskites [76], metal oxides [26,77], plus more recently organic resorcinarene hexamer [78], alloy nanoparticles [79] and metal organic frameworks [80,81]. There is a need for further extensive studies on the complex interactions between organic structure directing agents and metal cations to establish the role EPS plays in biomineralisation.…”
Section: Formation Mechanismmentioning
confidence: 99%